1987
DOI: 10.1002/cc.36819875808
|View full text |Cite
|
Sign up to set email alerts
|

Articulating secondary and postsecondary occupational programs

Abstract: This chapter presents essential concepts, strategies, and recommendations for implementing vertical articulation between occupational programs at high schools and two‐year colleges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, understanding what made these processes work or fail was seen as crucial as local consortia moved forward to implement tech-prep programs. Arnold (1987) suggested that institutions should review what type and how much articulation is needed before developing articulation programs. Arnold noted that articulation planning and implementation has an affect on three areas: administrative roles and relationships, curriculum design, and faculty and staff.…”
Section: Secondary Pupil Servicesmentioning
confidence: 99%
“…Therefore, understanding what made these processes work or fail was seen as crucial as local consortia moved forward to implement tech-prep programs. Arnold (1987) suggested that institutions should review what type and how much articulation is needed before developing articulation programs. Arnold noted that articulation planning and implementation has an affect on three areas: administrative roles and relationships, curriculum design, and faculty and staff.…”
Section: Secondary Pupil Servicesmentioning
confidence: 99%